Penggunaan Alat Pengering Berbahan Bakar Gas LPG dalam Pengeringan Tumpeng Beras - Kasmawan, I Gde Antha; Yuliara, I Made; Ratini, Ni Nyoman; Artawan, I Nengah; Trisnawati, Ni Luh Putu; Widagda, I Gusti Agung; Baskoro, Winardi Tjahyo (Bumi Lestari; Vol 25 No 1 (2025), 2025)
Rice obtained from grain mills can generally be categorized into whole rice and broken rice (mincid). The market price for mincid rice is usually cheaper (around 50%) than whole rice. The economic value of mincid rice can be increased by processing it into tumpeng which are usually used as a complementary means in Balinese Hinduism. However, the problem of drying tumpeng often occurs during the rainy season or when humidity is high which can cause mold to grow in the tumpeng , thereby reducing the quality of the tumpeng . To overcome this problem, the use of a dryer is essential. The tool is made with a portable design using metal and wood measuring 60 x 50 x 120 cm³ and uses a heater from an LPG (Liquefied Petroleum Gas) stove. The dryer can be used to dry around 6 kg of tumpeng with a drying duration of around 10 hours continuously. LPG gas consumption during the drying process is around 1.2 kg and the resulting dry product shrinks by almost 40% from the initial weight of the tumpeng . Based on the questionnaire distributed, 90.5% of users stated that they were satisfied with the use of the tool because it was considered more efficient and practical